Investigation of the fatigue crack growth behavior of S355 steel weldments of motor hangers of high-speed trains. (October 2022) - Mao, Liyong; Wang, Wenjing; Liu, Zhiming; Sha, Miao; Zhang, Dayong
Highlights: FCGR parameters of S355J2W have been measured and this paper provides essential data for fatigue assessment of bogie using S355J2W. 3D crack propagation analyses with constant amplitude loading are employed. The calculated crack growth path is in good agreement with the real crack. The results show that mode I plays an indisputable leading role in the crack propagation of the studied weld details of motor hanger in this paper, even if the crack growth is the result of the mixed-modes. Fatigue life of motor hangers are predicted by numerical simulation. This paper provides a reference for obtaining more reliable inspection periods for the motor hanger structure. Abstract: The behavior of fatigue cracks in welded details of motor hangers is investigated through crack growth numerical simulation under constant amplitude loading. The fatigue crack growth rate (FCGR) parameters of S355J2W steel are measured. FCGR tests are conducted on compact tension (CT) specimens. FCGR increases as the stress ratio increasing. Test data are compared with the reference curve of standards IIW and BS7910. Crack growth calculating results under mode I and mixed-modes conditions are compared. The crack growth path by simulation is in good agreement with the real crack path. The results also revealed that, even though fatigue cracks in the motor hanger are usually caused by mixed-modes conditions, mode I still governs the propagation.